Multidimensional Measurement of Richness and the Role of Income and Wealth - Nico Pestel; Andreas Peichl (Verein für Socialpolitik, 2010)
Closely following recent innovations in the literature on the multidimensional measurement of poverty, this paper provides similar measures for the top of the distribution using a dual cutoff method to identify persons, who can be considered as rich in a multidimensional setting. Thereby, the derived measures do not only take into account the number of individuals' affluent dimensions, but are also sensitive to changes in achievements of the rich. We make use of this framework to analyze the role of wealth, in addition to income, as one dimension of multidimensional well-being. In addition we analyze the roles of health and education. We provide empirical evidence for Germany.
Keywords: D31; D63; I10; 330; measurement of richness; multidimensional richness; income; wealth; health; education; Germany